HUMAN CAPITAL MANAGEMENT Mencapai Nilai Tambah Melalui Sumberdaya Manusia - Suharto, Suharto (JURNAL AKUISISI, 2011)
This paper aims to determine the role of human capital within an organization. The issue is whether human capital can improve employee performance and organization within a company. Based on the theory that were examined, human capiÂtal was able to improve employee performance and organization to deal with competitors. Because the concept of human capital is to add the value of human resources to improve overall organizational performance. Besides human capital is also a combination of intelligence, skills, behaviors, owned by workers and become the character that ensures long-term organizational life. Human capital can also be used as documentation (records) and to meet all the needs of the organizations information to determine whether any regulations or to predict the needs of the organization. The information was used to manage more deeply in order to be useful and lead to the future.